The Importance of Financial Literacy in Financial Management in Micro, Small and Medium Enterprises (MSMEs) - Dwyanti, Dwyanti (Journal of Applied Management and Business, 2024)
This research examines the impact of financial literacy on the financial management of Micro, Small, and Medium Enterprises (MSMEs) by building upon previous studies. A robust level of financial literacy within MSMEs is crucial for enhancing the effectiveness of financial management practices. Literature review indicates that a heightened understanding of fundamental financial concepts empowers MSMEs to make informed financial decisions, contributing to their overall resilience and sustainability. A deeper comprehension of financial management aids MSMEs in identifying financial opportunities and mitigating risks when formulating long-term financial strategies. Collaborative efforts involving various stakeholders, such as government bodies, financial institutions, and non-government organizations, are essential to elevate financial literacy among MSME stakeholders. It is anticipated that this literacy enhancement will positively impact the welfare and sustainability of the MSME sector as a whole, fostering local economic growth.